Gender equity in leading a South African private higher education institution - Verbooy , C.; Moyo, Z. (South African Journal of Higher Education, 2025)
There is a scarcity of research focusing on gender equity in higher education leadership in the African context or reference to the standing of gender equity in the private higher education institution. Thus, this study sought to explore gender equity in leading a South African private higher education institution. Using a generic qualitative research approach, data collection was undertaken using semi-structured interviews, and a focus group with eight institutional leaders from a South African private higher education institution. The data from the study revealed that gender stereotypes persist in private higher education institutions, defining which roles women must hold and how they must be managed and regarded inside the institution. As demonstrated by the study’s findings, there is no clear policy on leadership appointments, which leads to unfair practices in selecting leaders, such as an old boys club that advances male leaders. As a result, defining leadership and its responsibilities and context becomes significant. It is recommended that South African private higher education institutions establish a comprehensive, transparent policy on leadership and the support thereof, recognising the dual track faced by women in the policy to advance gender equity in the leading of these institutions.